Determining “Best Interests” in End-of-Life Decisions for the Developmentally Disabled: Minnesota State Guardians and Wards - Schuster, Mary Lay; Russell, Ann L.; Bartels, Dianne; Kelly-Trombley, Holli (Disability Studies Quarterly, 2014)
Abstract In this article, we report the results of a study of 129 case files and 16 guardian interviews on end-of-life decision making for Minnesota state wards who are developmentally disabled and are seldom competent to assert their wishes. We review the legal cases, legislative statutes, and professional standards that guide public guardians in deciding whether to begin, continue, or withdraw or withhold life-sustaining medical treatment from their wards. In particular, we reveal how the guardians' recommendations to the state Public Guardianship Administrator include such ableist assumptions as "normal," "natural," and "reasonable," but we also recognize the guardians' resistance to mind/body dichotomies and their expertise in determining quality of life in the context of how their wards live those lives.